2001
DOI: 10.1159/000047488
|View full text |Cite
|
Sign up to set email alerts
|

The Value of a Baseline Caries Risk Assessment Model in the Primary Dentition for the Prediction of Caries Incidence in the Permanent Dentition

Abstract: To establish a reliable screening method for caries prediction and to identify predominant risk factors, this study tested whether a cross–sectional caries risk model assessed at age 7 could be used to predict future caries onset in the permanent first molars at age 10 in 3,303 children born in 1989. As prediction variables, assessing the believed risk, baseline data at age 7 on oral health status, oral hygiene level, oral health behaviour and sociodemographic factors were used. The real risk, based on data co… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

7
50
1
6

Year Published

2005
2005
2014
2014

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 65 publications
(70 citation statements)
references
References 18 publications
7
50
1
6
Order By: Relevance
“…Vanobbergena et al found that occlusal and buccal plaque indices were highly significant for having a high caries increment in permanent first molars. (8) Basir et al believed that high oral hygiene index cannot increase the rate of permanent first molar caries. (12) However, reports suggest that dental plaque is a location for accumulation of cariogenic microorganisms and so we cannot ignore its role in dental caries.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Vanobbergena et al found that occlusal and buccal plaque indices were highly significant for having a high caries increment in permanent first molars. (8) Basir et al believed that high oral hygiene index cannot increase the rate of permanent first molar caries. (12) However, reports suggest that dental plaque is a location for accumulation of cariogenic microorganisms and so we cannot ignore its role in dental caries.…”
Section: Discussionmentioning
confidence: 99%
“…(7) According to J. Vanobbergen et al none of the socio-demographic and behavioral variables had enough predictive power at community level to be useful in identifying caries susceptible children. (8) The aim of this study was to find whether dmft, oral hygiene and dietary habits of children with caries in permanent first molars are different from those with healthy first molars?…”
Section: Introductionmentioning
confidence: 99%
“…The preventive measures include: diet and plaque control (mechanical and chemical methods), use of fluorides (systemic and topical), pit and fissure sealants (Harris & García-Godoy, 1999;Featherstone, 2000;Axelsson, 2000Axelsson, , 2004Gussy, et al, 2006). Furthermore, strategies to control the disease through risk assessment have been developed, which have also been extensively investigated (Vanobbergen, et al, 2001;Pearce, et al, 2002;Bratthall & Hänsel Petersson, 2005;Featherstone, et al, 2007;Ramos-Gomez, et al, 2010;Gao, et al, 2010). On the other hand, the advance of technology has also developed tools for the proper diagnosis of the lesion incipient such as DIAGNOdent and QLF (Stookey, 2004;Berg, 2007;Tranaeus, et al, 2007) as well as the need to detect in epidemiological studies noncavitated lesions (Ismail, et al, 2007).…”
Section: Dental Cariesmentioning
confidence: 99%
“…10 Anak yang berisiko karies tinggi mempunyai oral hygiene yang buruk ditandai dengan adanya plak pada gigi anterior disebabkan jarang melakukan kontrol plak. 5,11,12 Indikator risiko karies Risiko rendah Risiko sedang Risiko tinggi Guidelines on the use of pit and fissures sealants in paediatric dentistry: an EAPD…”
Section: Kontrol Plakunclassified